Reflections on Seeing HUG - Martin, Emily (Disability Studies Quarterly, 2012)
The following is a discussion of the film, HUG, a 2009 Sundance Official Selection. The plot of HUG focuses on when Asa, friend and manager, realizes musician Drew is off his meds, and the cross-town drive to sign his contract becomes significantly more complicated. Keywords: psychosis, sound, race, masculinity, disability